Apology strategies used by hotel management students in response to conflicts and challenges - Abdul Latiff Janaton, Noor Aqilah (2021)
Communication is deeply intertwined in the hotel industry. Besides providing services, one cannot imagine how the industry can thrive without communication as it plays a very vital in establishing and representing the success of a hotel. Therefore, a tactical approach in communication is important to prevent further complaint or guest dissatisfaction. Apology as politeness has received countless attention in speech acts research as it is essential in human interaction. Lack of apology and politeness awareness could lead to inappropriate apology and perceived as rude by the hearer. Previously published research was conducted in several areas such as hospital, novel and daily routine. As to fulfill the research gap, the researcher found out it is vital for the researcher to carry out about apology strategies in the English language used by Diploma Hotel Management students. The qualitative data were collected through a discourse completion test (DCT) consisted of three severity of offense variable (low, medium and high severity of offense) from 30 respondents who currently undergoing practical training in a hotel in Klang Valley. Respondents were given 30 minutes to complete the DCT. Apology strategies and politeness strategies were used as a framework to analyse and interpret for apology strategy and politeness strategies by using frequencies and percentage. Finding shows respondents prefer to use numbers of apology strategies instead of only use “expression of regret” apology strategies. In terms of politeness, respondents used both negative and positive politeness as to maintain harmony to the guest and results also showed the severity of offense plays an important role in the choices of apology strategies. The findings of this research might be helpful and significance to hotel industries, educators, teachers, students and those who are interested in pragmatics in general and apology act in specific.